Public relations writing : strategies and structures - Newsom, Doug; Haynes, Jim (Cencage Learning, 2017)
Providing the best of practical tools, real-world examples and proven theories, PUBLIC RELATIONS WRITING: STRATEGIES & STRUCTURES, 11th Edition, teaches you the essentials of writing with understanding and purpose. Extremely student friendly, it guides you step by step through a logical progression of PR writing, starting with the roles and responsibilities of the PR writer, followed by writing principles, preparing to write, writing for select audiences, and writing for crisis situations. It thoroughly explains the different styles and techniques behind writing principles. The Eleventh Edition also includes an entire chapter devoted to writing for social media